2014
DOI: 10.1111/iju.12460
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of the prostate after radiotherapy for prostate cancer: Impact on quality of life

Abstract: Abbreviations & AcronymsObjectives: To evaluate the impact of transurethral resection of the prostate on quality of life after radiotherapy for prostate cancer. Methods: A group of 49 consecutive patients with and 487 without prior transurethral resection of the prostate responded to the Expanded Prostate Cancer Index Composite questionnaire before, on the last day, and a median time of 2 months and 16 months after external beam radiotherapy (70-78 Gy). A matched-pair analysis was used to avoid the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several studies have proposed that TURP was a predictor of decline in urinary QOL and GU morbidity in photon external radiotherapy [2729]. This suggestion is based on the fact that TURP induces long-term structural damage to the urethra in the prostate, and photon radiation might have additive effects on the lesions [28, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed that TURP was a predictor of decline in urinary QOL and GU morbidity in photon external radiotherapy [2729]. This suggestion is based on the fact that TURP induces long-term structural damage to the urethra in the prostate, and photon radiation might have additive effects on the lesions [28, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Pinkawa et al, in a matched pair analysis, showed that patients undergoing TURP after EBRT have better urinary function score compared to patients who underwent EBRT alone. 2 On the other hand, Liu showed that these patients have a five-fold risk of incontinence compared to non-operated patients (5-year rate of 8% vs 1.5%, p=0.0015). 3 A rate of 27% new-onset incontinence was reported in another series.…”
Section: Introductionmentioning
confidence: 96%
“…In this issue of International Journal of Urology , Pinkawa et al . published a retrospective, matched‐pairs study titled “Transurethral resection of the prostate after radiotherapy for prostate cancer: Impact on quality of life” . A group of 49 patients with prior TURP who successfully completed EBRT was retrospectively compared with 487 patients without TURP; they were all treated in the same era at the authors' institution in Germany.…”
mentioning
confidence: 99%